Research and Development and Technology in the Philippines - Caesar B. Cororaton (Philippine Institute for Development Studies (PIDS), 2002)
Research and development (R&D) and technology are analyzed from the perspective of Philippine economic growth in the paper. It examines the productivity performance of the economy and analyzes how it has been affected by developments in R&D and technology. General R&D and technology policies and institutional structure and arrangements are examined. National, as well as specific sectoral gaps are identified, while weaknesses in institutional arrangements are highlighted. Insights for policy are derived from the analysis.
Keywords: 330; technology; research and development (R&D); Technologiepolitik; Forschung; Industrieforschung; Technologie; Wissenschaft; Innovation; Wirtschaftswachstum; Philippinen